2001
DOI: 10.1096/fj.01-0273rev
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL and HDL: antagonists in atherothrombosis

Abstract: Increased LDL oxidation is associated with coronary artery disease. The predictive value of circulating oxidized LDL is additive to the Global Risk Assessment Score for cardiovascular risk prediction based on age, gender, total and HDL cholesterol, diabetes, hypertension, and smoking. Circulating oxidized LDL does not originate from extensive metal ion-induced oxidation in the blood but from mild oxidation in the arterial wall by cell-associated lipoxygenase and/or myeloperoxidase. Oxidized LDL induces atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
248
0
21

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(276 citation statements)
references
References 138 publications
7
248
0
21
Order By: Relevance
“…Oxidized LDL generated by oxidative stress also promotes the progression of arteriosclerosis. [27][28][29] In this study, plasma HSCRP and MDA-LDL levels were lower with azelnidipine than with thiazide therapy. The antioxidant effect of azelnidipine possibly participated in the reduction of plasma MDA-LDL levels.…”
Section: Combined Antihypertensive Therapy With Olmesartan T Ishimitsmentioning
confidence: 60%
“…Oxidized LDL generated by oxidative stress also promotes the progression of arteriosclerosis. [27][28][29] In this study, plasma HSCRP and MDA-LDL levels were lower with azelnidipine than with thiazide therapy. The antioxidant effect of azelnidipine possibly participated in the reduction of plasma MDA-LDL levels.…”
Section: Combined Antihypertensive Therapy With Olmesartan T Ishimitsmentioning
confidence: 60%
“…Indeed, ox-LDL was found to induce metalloproteases, which degrade matrix proteins, important for SMC migration, and, in addition, ox-LDL induces SMC apoptosis. 36 It has been shown that Pparg exerts anti-inflammatory actions by antagonizing the transcriptional activity of Nfkb1. 37 Accordingly, stevioside-treated mice showed a lower Nfkb1/Nfkbia ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis has been documented as an inflammatory disease and is associated with increased O 2 ·-and other ROS (Griendling et al 2000b;Patel et al 2000a;Patel et al 2000b;Mertens et al 2001;Harrison et al 2003b;Lassegue et al 2003;Wassmann et al 2004). Possible signaling mechanisms for the inflammatory based reaction are discussed in section 2.3.…”
Section: Atherosclerosismentioning
confidence: 99%
“…It may play a role in the oxidation of LDL and formation of lipid free radicals, which are capable of scavenging NO (Parthasarathy et al 1989;Mertens et al 2001). Lipoxygenase is also thought to contribute to angiotensin II activation of NADPH oxidase O 2 ·-formation during cardiovascular disease (Luchtefeld et al 2003).…”
Section: Lipoxygenasementioning
confidence: 99%